MENGINTEGRASIKAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN DI SD SWASTA PANGERAN ANTASARI HELVETIA 2022 - Rahmadhani Siregar, Siti Rahmadhani Siregar; Sugito; Danis, Amir; Mardame Simamora, Saut; Ramadhani, Sri (Transpublika Publisher, 2022)
Character is a foothold of knowledge and skills. Knowledge and skills without the right personality foundation will be misleading and destructive. The character in the form of personality is owned through the educational process. The role of the teacher helps in shaping the character of students by providing examples, ways of speaking or delivering good material, tolerance, and various other related matters. The researcher uses an approach method with training activities in this community service. The conclusion stated that this training was quite successful where the trainees were very enthusiastic in training activities, this was also because each teacher had never received socialization from the government regarding government policies by providing Strengthening Character Education in Schools.